2010
DOI: 10.1182/blood-2009-12-257030
|View full text |Cite
|
Sign up to set email alerts
|

EGR-1 activation by EGF inhibits MMP-9 expression and lymphoma growth

Abstract: IntroductionRecent evidence has reinforced the notion that the tumor microenvironment plays a key role in the growth and survival of hematologic malignancies. [1][2][3] In this tumor microenvironment, cancer cells are surrounded by numerous cell types including endothelial cells (ECs) of the blood and lymphatic circulation, stromal fibroblasts and a variety of bone marrow-derived cells. 4 Stromal cells express a wide variety of chemokine and growth factor receptors, rendering them responsive to the local produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 59 publications
(70 reference statements)
2
33
0
Order By: Relevance
“…EGR1 has been reported to promote MMP9 expression in HeLa cell [11]. However, in lymphoma, EGR1 inhibits MMP9 expression by direct promoter binding [12]. Our data showed that exogenous EGR1 overexpression inhibited mRNA and protein expression of MMP9, which is consistent with the result in lymphoma.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…EGR1 has been reported to promote MMP9 expression in HeLa cell [11]. However, in lymphoma, EGR1 inhibits MMP9 expression by direct promoter binding [12]. Our data showed that exogenous EGR1 overexpression inhibited mRNA and protein expression of MMP9, which is consistent with the result in lymphoma.…”
Section: Discussionsupporting
confidence: 82%
“…Previous study showed that EGR1 inhibits MMP2 expression by direct promoter binding in human breast cancer cell [10]. EGR1 has been reported to promote MMP9 expression in HeLa cells [11], but to inhibit its expression in lymphoma [12]. It has been known that MDM2 promotes metastasis of breast cancer by upregulating MMP9 [13].…”
Section: Introductionmentioning
confidence: 99%
“…ECM remodeling and degradation by metalloproteinases, which is associated with cancer growth and invasion, is likely to lead to the release of ECM components that can act as "soluble" pep- tides within the tumor microenvironment. T cell malignancies are also associated with metalloproteinases and ECM remodeling as well as dissemination (41)(42)(43)(44). Thus, our study suggests that the ColI released from tissue ECM can bind to ␣2␤1 integrin and provides T-ALL cells with a survival advantage against the cytotoxic effect of doxorubicin.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, there were several interesting genes involved in the transcriptional misregulation of cancer, such as Runx2 , Mmp3 , Mmp9 , Egln3 and Vegfa . [8083] We also found upregulation of the Id2 transcript in iNKT tumors as compared to premalignant iNKT cells (Figure 8B). This could represent overexpression of Id2 exon 3, which is the only remaining exon in Id2 f/f mice.…”
Section: Resultsmentioning
confidence: 60%